Literatur Review : Metode Analisis Identifikasi Kualitatif dan Kuantitatif Morfin Dalam Sampel Urine - Nina Elyyana; Sepvia Putri Sukma Wibowo; Tiara Nurayuni; Marsah Rahmawati Utami; Lina Nurfadhila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Opioids are one type of narcotics that are depressant, function to reduce the functional activity of the body. Morphine is one of the classes of strong opioids that functions as a strong analgesic that is usually used in patients with severe pain such as postoperatively. Morphine has additive properties and can cause toxic effects, so it is necessary to analyze morphine in the sample. Morphine analysis is performed using biological samples such as urine. This study aims to provide an explanation of various methods in the analysis of morphine substances in urine samples both qualitatively and quantitatively. The method used in writing this scientific paper is in the form of a literature study conducted by collecting relevant journals in the period of February-June 2023. The databases used are Google Scholar and Pubmed. Based on the results of the journal review, morphine identification in biological urine samples can be done quantitatively and qualitatively by several methods, namely Rapid Diagnostic Test, Card Test, KLT, LC-MS, GC-MS, SPRi, CFIA, Spectrophotodensitometry, MS and HPLC. Methods can be adapted to each need and condition.